Synthesis and Morphological Characterization of Nanocomposite Based on Anodic tio2 Nanotubes and Poly(N-Maleoyl Glycine-Co-Acrylic Acid) - Sanchez-Poblete, J (Sociedad Chilena de Quimica, 2017)
In this study, we examined the synthesis, and characterization of TiO2/poly(N-maleoylglycine-co-acrylic acid) (TiO2/poly(MG-co-AA)) nanocomposite. The nanocomposite was prepared by the dispersion of TiO2 nanotubes in a water solution of the polymer (3% w/w) and then it was lyophilized. The nanocomposite was characterized by FTIR and Raman spectroscopies. The incorporation of TiO2 nanotubes to the polymeric matrix was determined by transmission electron microscopy (TEM) from which TiO2 nanotubes in the inner of copolymer with diameters ranging between 90 and 100 nm were observed. The overall morphology of the previously synthetized nanotubes was determined by scanning electron microscopy (SEM). For the nanocomposite system, the morphology was studied by atomic force microscopy (AFM) from which a grain shape structure was observed. This process resulted in a new nanocompsite material with an average grain diameter estimated by SEM and AFM ranging between 210-240 nm. It was observed that the nanotubes were homogeneously dispersed within the polymeric matrix. The prepared material could be suitable in the design of electronic devices and additionally could have potential applications as biomaterial.